(3SjQI GdEOQjSi GdSjO YHO GdYRjR Hf eSYhO GdOHGZ hefGbHg GdeJhaj SfI (B1131(3g`s - (3CHh GdYHGS CMeO Hf eHGQc Hf eMeO GdSLdeGSj GddeWj,J (B1156 (3g` s ((3CMeO Hf eMeO CHj GdfhQ GdcjGdi GdQaGYi s)
(3ChdgG (B:s
(3CeG HYO ,aEfg deG ef Gddg Ydi HeYQaI GdcGed YHO GdYRjR Hf ehdGfG hSjOfG eSYhO (B,(3deG cGf QLH SfI JSY hYTQjf heGFI hCda Cdgefi Gddg Edi JbjjO HYV ahGFFFFFOg dJJe Hg G daGFOI s
(3BNQgG (B:s
(3Je hGfJgi eG cJHg SjOfG CHh GdYHGS TgGH GdOjf CMeO Hf eHGQc GdSLdeGSi s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B201 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B56s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B236 ; (3agQSJ GdNRGfI GdYGeI HGdQHGW (B- (3GdLRA (B2 - (3U (B216 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs